My Wage is Unfair! Just a Feeling or Comparison with Peers? - Stefan Schneck (Review of Behavioral Economics, 2014)
This paper analyzes the nexus between income comparisons and perceptions of unfair pay. We apply a large German household survey and conduct wage regressions to conclude whether individuals who perceive their wages as unfair earn significantly lower wages than fairly paid individuals with similar characteristics. We find that unfairly paid individuals earn significantly less than fairly paid counterparts. This suggests that unfairness perceptions with respect to wages are based on sound income comparisons with peers. We also contribute findings to the literature on reference points. When asked about a subjectively fair amount in Euros, unfairly paid individuals tend to claim much higher wages than fairly paid individuals with identical characteristics. Wage claims, thus, rest on additional factors.
Keywords: J30; J31; 330; Fairness; Wages; Reference points; Wages